A Predictive Model of the Optimal Tool Edge Geometry for Veneer Cutting Processes. Issue 5 (3rd September 2019) - Bouarab, Fatma Zohra; Aknouche, Abdelhamid H.; Hamrani, Abderrachid
Abstract: Veneer cutting is a specific machining process, where the chip is the final product. The objective of this article is to investigate on the optimal tool edge geometry, using particle swarm optimization (PSO) algorithm, to obtain the desired veneer thickness. The challenge is to maintain the best quality of veneer product with the control of pre-splitting condition and thickness variation. Numerical results obtained from PSO algorithm are compared and verified with the experimental ones. The proposed model allows us to predict the characteristic tool angles for different chip thicknesses and friction coefficients. For chip thickness range greater than 2 mm, the presplitting condition is no longer satisfied, as in the case of rotary peeling veneer, the need of using pressure bar becomes primordial.